2018
DOI: 10.29132/ijpas.354885
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Some Extraction Solvents on the Antioxidant Properties of Strawberry Fruit

Abstract: In this paper, antioxidant activity of strawberries extracted with different solvents was investigated since they are consumed by people due to their anticancer, anti-atherosclerotic, anti-inflammatory and anti-neurodegenerative properties. For this purpose, different acidified extraction solvents such as water (ES1), acetone (ES2), acetonitrile (ES3), methanol (ES4) and ethanol (ES5) were used in extraction process of strawberries. The effects of different extraction solvents on the antioxidant activity were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…We determined the antioxidant activity of Vitis sylvestris Gmelin using DPPH and ABTS radical scavenging activities and total phenolic content tests, applying these tests to the extracts of the samples processed with water, acetonitrile and methanol, and evaluated the results statistically. There is a mention in a literature report that antioxidant activity results changed significantly depending on the solvent type (24)(25)(26)(27). In the current study, we applied the antioxidant activity and total phenolic content test applied to different extracts; we obtained the highest results for all tests with methanolic extracts.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…We determined the antioxidant activity of Vitis sylvestris Gmelin using DPPH and ABTS radical scavenging activities and total phenolic content tests, applying these tests to the extracts of the samples processed with water, acetonitrile and methanol, and evaluated the results statistically. There is a mention in a literature report that antioxidant activity results changed significantly depending on the solvent type (24)(25)(26)(27). In the current study, we applied the antioxidant activity and total phenolic content test applied to different extracts; we obtained the highest results for all tests with methanolic extracts.…”
Section: Resultsmentioning
confidence: 70%
“…The results in the presented study were compatible with those found in the literature. Researchers determined that the data changed importantly depending on different conditions such as drying method, extraction method, and solvent type, as stated in the literature (24)(25)(26)(27)30).…”
Section: Resultsmentioning
confidence: 99%
“…The antioxidant properties of natural foods are generally examined by traditional extraction methods. As stated in the literature, extraction conditions that significantly affect the analysis results should be examined in the investigation of the antioxidant properties of natural foods (Boulekbache‐Makhlouf et al., 2013; Cvetanovic et al., 2015; Ghasemzadeh et al., 2015; Hussain et al., 2012; Karaaslan et al., 2018, Karaaslan Ayhan, 2020; Moo‐Huchin et al., 2019; Monteiro et al., 2020; Zlabur et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…One of the conditions that significantly affect the extraction efficiency and analysis results is the extraction method (Chanda & Kaneria, 2012; Hussain et al., 2012; Li et al., 2007). Another condition as important as the extraction method is the type of extraction solvent (Boulekbache‐Makhlouf et al., 2013; Chanda & Kaneria, 2012; Hussain et al., 2012; Karaaslan et al., 2018). For the extraction process, organic solvents with polar character (e.g., water, methanol, acetone, ethanol, and acetonitrile) are used, and methanol is widely preferred among organic solvents (Karaaslan & Yaman, 2018; Navas et al., 2012; Nguyen et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Plants have developed mechanisms that protect themselves against the damage caused by ROS. These mechanisms consist of clearance of ROS by nonenzymatic antioxidants and enzymatic antioxidant (Karaaslan et al, 2018;Sarker and Oba, 2020). By reducing the chlorophyll content of plants under stress, the photosynthesis content is reduced.…”
Section: Introductionmentioning
confidence: 99%